ChatGPT y la superficialidad del conocimiento: implicaciones académicas y éticas en el siglo XXI - Estrada García, Alex (2024)
The present research examines the possible implications of AI, specifically chatGPT, in the academic context, as well as in social relations and its influence on the human condition in the light of ethics and the techno-scientific advances of the 21st century. Digital technology from its beginnings constituted a new way of understanding reality, or at least what is understood as reality. Therefore, events such as the emergence of AI programs demand thinking about the nature and scope of knowledge that is created and innovated in multiple scenarios. It also confronts society with uncertainties related to a future governed by increasingly sophisticated machines and software. The approach to the exposed issues will be carried out through the philosophical approach of Husserlian phenomenology, this approach enables the understanding, description and analysis of the experiences, perceptions and expectations that arise when using technology in academic contexts; likewise, it makes it feasible to reflect on how the interaction with AI has an impact on the understanding and construction of knowledge, considering the conscious experience of humans. In conclusion, the application of AI in the academic context demands an ethical responsibility, especially in the automated creation of certain academic tasks through AI programs, as well as the impact it has on social relations, seen as a new way of looking at the other through the mirror of technology.